2005
DOI: 10.1017/s1092852900024500
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Carbamazepine Extended-Release Capsules in Bipolar Disorder

Abstract: Carbamazepine (CBZ) has long been a therapeutic option for bipolar disorder. Carbamazepine extended-release capsules (CBZ-ERC) are a recent formulation of CBZ approved by the US Food and Drug Administration in 2004 for the treatment of acute manic and mixed episodes associated with bipolar I disorder. This new formulation was developed to improve dosing convenience and decrease daily fluctuations in serum CBZ concentration, thereby lowering the incidence of adverse events. Two randomized, double-blind, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
(58 reference statements)
1
6
1
Order By: Relevance
“…At this time, several small studies reported the anti-manic effects of carbamazepine as well as its prophylactic effects against the recurrence of manic and depressive episodes in patients with bipolar disorder. Over the last several decades, many double-blind, controlled trials demonstrated the efficacy of carbamazepine in the treatment of acute mania in bipolar disorder, with response rates similar to those of lithium [10]. Early controlled trials of carbamazepine in the treatment of acute mania were conducted with conventional immediate-release formulations and confounded by co-administration with lithium or standard antipsychotics [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At this time, several small studies reported the anti-manic effects of carbamazepine as well as its prophylactic effects against the recurrence of manic and depressive episodes in patients with bipolar disorder. Over the last several decades, many double-blind, controlled trials demonstrated the efficacy of carbamazepine in the treatment of acute mania in bipolar disorder, with response rates similar to those of lithium [10]. Early controlled trials of carbamazepine in the treatment of acute mania were conducted with conventional immediate-release formulations and confounded by co-administration with lithium or standard antipsychotics [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, many double-blind, controlled trials demonstrated the efficacy of carbamazepine in the treatment of acute mania in bipolar disorder, with response rates similar to those of lithium [10]. Early controlled trials of carbamazepine in the treatment of acute mania were conducted with conventional immediate-release formulations and confounded by co-administration with lithium or standard antipsychotics [10]. But, the established correlation between fluctuations in serum levels of carbamazepine and intermittent side effects helped prompt the development of extended-release formulations of carbamazepine for use in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 As an oral preparation, CBZ has a well-established therapeutic profile with nearly 40 years of clinical use in the United States and around the world. 3 Concerning its crystal structures, CBZ crystallizes in four different anhydrous polymorphs. A complete list of references, with the different nomenclature of these four CBZ polymorphs, can be found in the work of Grzesiak et al 4 Moreover, CBZ can form a dihydrate 5,6 and several cocrystals or molecular adducts.…”
Section: Introductionmentioning
confidence: 99%